Hepatic Glucose Output Inhibition by Mexican Plants Used in the Treatment of Type 2 Diabetes - Mata-Torres, Gerardo; Andrade-Cetto, Adolfo; Espinoza-Hernández, Fernanda Artemisa; Cárdenas-Vázquez, René (Frontiers in Pharmacology, 2020)
De novo hepatic glucose production or hepatic gluconeogenesis is the main contributor to hyperglycemia in the fasting state in patients with type 2 diabetes owing to insulin resistance, which leads to at least twice as much glucose synthesis compared to healthy subjects. Therefore, control of this pathway is a promising target to avoid the chronic complications associated with elevated glucose levels. Patients with type 2 diabetes in the rural communities of Mexico use medicinal plants prepared as infusions that are consumed over the day between meals, in several of these plants the presence of phenolic acids able to block the enzyme glucose-6-phosphatase is reported. Following this rationale, one approach to understanding the possible mechanism of action of medicinal plants is to assess their capacity to inhibit hepatic glucose production. In the present work, extracts of Ageratina petiolaris, Bromelia karatas, Equisetum myriochaetum, Rhizophora mangle and Smilax moranensis, which are Mexican plants that have been traditionally used to treat type 2 diabetes, were assayed to evaluate their possible hepatic glucose output inhibitory activity with a pyruvate tolerance test in 18 h fasted STZ-NA Wistar rats after oral administration of the extracts. In addition, the in vitro effects of the extracts on the last hepatic glucose output rate-limiting enzyme glucose-6-phosphatase was analyzed. Our results showed that four of these plants had an effect on hepatic glucose production in the in vivo or in vitro assays. A. petiolaris and R. mangle extracts decreased glucose output, preventing an increase in the blood glucose levels and sustaining this prevented increase after pyruvate administration. In addition, both extracts inhibited the catalytic activity of the glucose-6-phosphatase complex. However, even though S. moranensis and B. karatas did not exhibit a significant in vivo effect, the former had the most potent inhibitory effect on this enzymatic system, while the E. myriochaetum extract only inhibited hepatic glucose production in the pyruvate tolerance test. Because of the traditional method in which diabetic patients use plants, hepatic glucose production inhibition seems to be a mechanism that partially explains the common hypoglycemic effect.